Synthetic Biology Omics Tools and Their Applications (Springer Singapore, 2018)
The book uses an integrated approach to predict the behavior of various biological interactions. It further discusses how synthetic biology gathers the information about various systems, in order to either devise an entirely new system, or, to modulate existing systems. The book also tackles the concept of modularity, where biological systems are visualized in terms of their parts. The chapters discuss how the principles of engineering are being used in biomedical sciences, to design biological circuits that can harbor multiple inputs and generate multiple outputs; to create genetic networks and control gene activity, in order to generate a desired response. The book aims to help the readers develop an array of biological parts, and to use these parts to develop synthetic circuits that can be assembled like electronic circuits. The ultimate aim of the book will be to serve as an amalgamation of key ideas of how judiciously synthetic biology could be exploited in therapeutic device and delivery mechanism.